No clinical benefit in mortality associated with hydroxychloroquine treatment in patients with COVID-19. (March 2021) - Sands, Kenneth; Wenzel, Richard; McLean, Laura; Korwek, Kimberly; Roach, Jonathon; Miller, Karla; Poland, Russell E.; Burgess, L. Hayley; Jackson, Edmund; Perlin, Jonathan B.
Highlights: Hydroxychloroquine was proposed as a treatment for COVID-19 in the early pandemic. Data from 1669 COVID-19 patients in the United States was analyzed. Hydroxychloroquine was associated with an increased risk of mortality. Abstract: Background: The use of hydroxychloroquine (HCQ), with or without concurrent administration of azithromycin (AZM), for treatment of COVID-19 has received considerable attention. The purpose of this study was to determine whether HCQ administration is associated with improved mortality in COVID-19 patients. Methods: We conducted a retrospective analysis of data collected during the care process for COVID-19 positive patients discharged from facilities affiliated with a large healthcare system in the United States as of April 27, 2020. Patients were categorized by treatment with HCQ (in addition to standard supportive therapy) or receipt of supportive therapy with no HCQ. Patient outcomes were evaluated for in-hospital mortality. Patient demographics and clinical characteristics were accounted for through a multivariable regression analysis. Results: A total of 1669 patients were evaluated (no HCQ, n = 696; HCQ, n = 973). When adjusting for patient characteristics, receipt of AZM, and severity of disease at admission, there was no beneficial effect of receipt of HCQ on the risk of death. In this population, there was an 81% increase in the risk of mortality among patients who received HCQ at any time during their hospital stay versus no HCQ exposure (OR: 1.81, 95% CI: 1.20–2.77, p = 0.01). Conclusions: In this retrospective analysis, we found that there was no benefit of administration of HCQ on mortality in COVID-19 patients. These results support recent changes to clinical trials that discourage the use of HCQ in COVID-19 patients.